The Multiple Intelligences Dimension In Indonesia`s Religious Education - Anisa Dwi Makrufi; Muhammad Risydan Arum Bagas Prihatno (Al-Hayat Al-Istiqomah Foundation, 2020)
The implementation of the 2013 curriculum as a reference in the education process in Indonesia also impacts on the learning model of religious education. The current education curriculum accommodates students' multiple intelligences. This paper aims to uncover the dimensions and implementation of Islamic Religious Education (PAI) curriculum based on multiple intelligences at the Elementary School level. This study uses a qualitative approach to the type of library research. The results showed that the dimensions of multiple intelligences in the 2013 PAI curriculum at Elementary School level can be seen through the classification of nine intelligences (according to Howard Gadner) in each section of core competence. Spiritual competence contains existential intelligence. Social competence is related to interpersonal and intrapersonal intelligence. In the aspect of knowledge includes logical-mathematical intelligence, linguistic intelligence, musical intelligence. On the other hand, competency skills contain visual-spatial intelligence, kinesthetic intelligence, and naturalist intelligence. Implementation of the concept of multiple intelligences in PAI 2013 curriculum learning can be done by recognizing students' multiple intelligences; preparing a draft of learning; develop learning models, and determine the multiple intelligence-based assessment models in the 2013 PAI curriculum at Elementary School level.